2009
DOI: 10.2478/v10009-009-0018-4
|View full text |Cite
|
Sign up to set email alerts
|

Centric diatoms (Coscinodiscophyceae) of fresh and brackish water bodies of the southern part of the Russian Far East

Abstract: Anotated list of centric diatoms (Coscinodiscophyceae) of fresh and brackish water bodies of the southern Russian Far East, based on the authors' data, supplemented by the published literature, is given. It includes 143 algae species (including varieties and forms -159 taxa) representing 38 genera, 22 families and 14 orders. * Corresponding autor: medvedeva@ibss.dvo.ru

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 5 publications
0
11
0
5
Order By: Relevance
“…Urosolenia eriensis var. morsa was found in countries such as Britain, New Zealand, Russia and Brazil (Medvedeva et al 2009, Tremarin et al 2009, Guiry & Guiry 2014.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Urosolenia eriensis var. morsa was found in countries such as Britain, New Zealand, Russia and Brazil (Medvedeva et al 2009, Tremarin et al 2009, Guiry & Guiry 2014.…”
Section: Resultsmentioning
confidence: 96%
“…Acanthoceras zachariasii is a freshwater taxon, worldwide distributed, recorded to Germany, Australia, Switzerland, Sweden, Finland, Russia, United States, Chile, Argentina and Brazil (Brun 1874, Hustedt 1930, Cleve-Euler 1951, Rivera 1974, Shirata & Valente-Moreira 1987, Ferrario et al 1992, Edlund & Stoermer 1993, Medvedeva et al 2009). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3). Most are cosmopolitan taxa and many can be found in lake environments across the middle to high latitudes of the northern hemisphere (van Dam et al 1994;Lotter and Biegler 2000;Bigler and Hall 2002;Kienel and Kumke 2002;Cremer and Wagner 2004;Smol et al 2005;Solovieva et al 2008;Medvedeva et al 2009;Rudaya et al 2009). The most abundant form is A. subarctica (20-60%), which also dominates in the nearby, 30-m-deep, silica-rich Two-Yurts Lake.…”
Section: Palaeoecology and Lake Developmentmentioning
confidence: 97%
“…This taxon has been identified from different trophic levels, ultraoligotrophic, oligotrophic, oligo-mesotrophic and meso-eutrophic (Cremer and Wagner, 2003). In addition, Krammer and Lange-Bertalot (1991a) and Medvedeva et al, (2009) announced that this taxon is ubiquitous. Our findings showed that the water of Karagöl Lake is slightly alkaline and has mesotrophic character.…”
Section: Diatom Taxa Compositionmentioning
confidence: 99%